Diagnosis about Integration process of youth foreign Catalan - Marta Sabariego Puig; Berta Palou Julián; Esther Luna González (Multidisciplinary Journal for Education, Social and Technological Sciences)
This paper presents the results of a diagnostic study on the real integration process of young migrants in Catalonia. The study was carried out using a descriptive survey of 3,830 young Catalans from varying cultural backgrounds aged between 14 and 18, with the aim of identifying the key factors influencing the integration of Catalan migrant youth. Also, in order to analyze these key elements in greater depth as factors easing and/or obstructing integration, four discussion groups were held with the same young people. Results reveal achievements and challenges for further study, useful for the design of social and educational policies which may promote the integration process, understood in its structural, social, cognitive-cultural and identitary dimensions. Our study confirms the need for a society with pluralistic beliefs, principles and actions, which should be reflected in democratic systems and social and educational policies based on the concept of integration as reciprocity.